Egr-1 is a key regulator of the blood-brain barrier damage induced by meningitic Escherichia coli - Ruicheng Yang; Xinyi Wang; Hulin Liu; Jiaqi Chen; Chen Tan; Huanchun Chen; Xiangru Wang (Cell Communication and Signaling, 2024)
Abstract Bacterial meningitis remains a leading cause of infection-related mortality worldwide. Although Escherichia coli (E. coli) is the most common etiology of neonatal meningitis, the underlying mechanisms governing bacterial blood-brain barrier (BBB) disruption during infection remain elusive. We observed that infection of human brain microvascular endothelial cells with meningitic E. coli triggers the activation of early growth response 1 (Egr-1), a host transcriptional activator. Through integrated chromatin immunoprecipitation sequencing and transcriptome analysis, we identified Egr-1 as a crucial regulator for maintaining BBB integrity. Mechanistically, Egr-1 induced cytoskeletal changes and downregulated tight junction protein expression by directly targeting VEGFA, PDGFB, and ANGPTL4, resulting in increased BBB permeability. Meanwhile, Egr-1 also served as a master regulator in the initiation of neuroinflammatory response during meningitic E. coli infection. Our findings support an Egr-1-dependent mechanism of BBB disruption by meningitic E. coli, highlighting a promising therapeutic target for bacterial meningitis.